Determination of the dynamic critical maneuvering area in an encounter between two vessels: Operation with negligible environmental disruption. (1st October 2020) - Gil, Mateusz; Montewka, Jakub; Krata, Przemyslaw; Hinz, Tomasz; Hirdaris, Spyros
Abstract: This paper introduces the concept of Collision Avoidance Dynamic Critical Area (CADCA) for onboard Decision Support System s (DSS). The indicator proposed is derived via identification of a minimum required maneuvering zone in an encounter between two vessels. The CADCA model accounts for ship maneuvering dynamics and associated hydrodynamic actions emerging from different rudder angles and forward speed effects. The method presented is novel as it considers the variability of a critical area due to dynamic changes in operational parameters for both vessels. Results of the simulations carried out in negligible weather conditions confirm that computed zones may differ significantly in terms of shapes and limits. It is demonstrated that the size of the CADCA depends on the rudder angle, forward speed, as well as the dimensions of the vessels. Highlights: A concept of Collision Avoidance Dynamic Critical Area (CADCA) has been proposed. CADCA is a required maneuvering zone determined for encountering ships. 6DoF ship motion model has been used to simulate realistic ship trajectories. CADCA adjusts its shape accordingly to operational parameters of vessels. CADCA differs depending on the dimensions and characteristics of encountering ships.